Analisis Konsep Integritas Jonathan Lamb dalam Menanggulangi Krisis Moral Kepemimpinan di Lembaga Pendidikan Kristen - Novita Kanda Lodo; Helda Nafrawanti Bissa; Friskila Sattoe; Mety Arma Pabalik; Wildyanti Wildyanti (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The moral crisis and rampant corruption among Christian leaders pose serious challenges that erode the credibility and integrity of religious institutions. This phenomenon not only tarnishes the image of Christianity institutionally but also weakens the foundation of ethics and spiritual values that should guide the lives of the congregation. This issue becomes even more pressing when it occurs in the realm of Christian education, a place where future leaders should be formed. This study aims to analyze Jonathan Lamb's concept of integrity as a strategic framework for addressing this crisis, especially in the context of Christian educational institutions. Using a qualitative approach and literature review, this study highlights Lamb's holistic view of integrity, which encompasses three main dimensions: wholeness of the person (wholeness), consistency between beliefs and actions (consistency), and full accountability to God (accountability to God). Lamb's concept of integrity is highly relevant amidst the increasing need for leaders who are not only competent but also possess proven character. The findings of this study indicate that to effectively implement the concept of integrity, Christian educational institutions need to take a two-pronged approach: first, comprehensively reform the curriculum so that integrity values are not only a separate subject, but are integrated into all disciplines and learning activities; Second, building an institutional culture that emphasizes moral exemplarity from leaders, lecturers, and educational staff. Furthermore, a sustainable character development system, transparent accountability evaluation, and open ethical discussion are needed. Education is not only about knowledge transfer, but also about character transformation. Therefore, integrity must be seen as the core of Christian education, not an add-on. This study concludes that Lamb's concept of integrity can be a transformative model that encourages the formation of future leaders with strong character, prevents moral failure, and restores public trust in Christian institutions